The Effect of Priming with Photographs of Environmental Settings on Walking Speed in an Outdoor Environment - Franěk, Marek; Režný, Lukáš (Frontiers in Psychology, 2017)
This study examined the effect of priming with photographs of various environmental settings on the speed of a subsequent outdoor walk in an urban environment. Either photographs of urban greenery, conifer forests, or shopping malls were presented or no prime was employed. Three experiments were conducted (N = 126, N = 88, and N = 121). After being exposed to the priming or no-priming conditions, the participants were asked to walk along an urban route 1.9 km long with vegetation and mature trees (Experiment 1, Experiment 3) or along a route in a modern suburb (Experiment 2). In accord with the concept of approach-avoidance behavior, it was expected that priming with photographs congruent with the environmental setting of the walking route would result in slower walking speed. Conversely, priming with photographs incongruent with the environmental setting should result in faster walking speed. The results showed that priming with the photographs with vegetation caused a decrease in overall walking speed on the route relative to other experimental conditions. However, priming with incongruent primes did not lead to a significant increase in walking speed. In all experimental conditions, the slowest walking speed was found in sections with the highest natural character. The results are explained in terms of congruency between the prime and the environment, as well as by the positive psychological effects of viewing nature.